Genotype-mutagenic interaction in the cytogenetic variability of winter wheat for a new ecogenetic factor - Horshchar, Vladyslav; Горщар, Владислав Іванович; Nazarenko, Mykola; Назаренко, Микола Миколайович (Дніпровський національний університет імені Олеся Гончара, 2023)
The study of cytogenetic parameters of the activity of new mutagenic factors aims to reliably establish the possibilities of these factors in terms of variability depending on the subject of mutagenic action, the optimal use of certain factor sizes, the combination of the selected protocol with optimization of the yield of mutant forms in the future. Seeds of eight varieties of winter wheat (Balaton, Borovytsia, Zeleny Gai, Zoloto Ukrainy, Kalancha, Niva Odeska, Polyanka, Pochayna) were treated by SA (sodium azide) at concentrations of 0.010%, 0.025%, 0.05%, 0.10%. They were soaked in water solution for 24 hours. Cytogenetic activity was evaluated by pollen sterility, evaluation of general rates and indicators of spectra of chromosomal abnormalities at medium phases of cell mitosis according to wheat variety and chemical agent concentrations. As a result of the study, the key importance of the genotype-mutagenic interaction was demonstrated within the limits of variability of the main indicators of the frequency and spectrum of chromosomal aberrations. It has been established that in the future it will be more optimal to use two varieties whose genotype-mutagenic specificity indicators are significantly higher and one should expect a more significant yield of promising mutant forms from them in the future, especially in combination with SA concentrations in the range of 0.025% and 0.05%. It is demonstrated that the main parameters that reflect genetically determined possibilities in susceptibility to the ecogenetic factor are pollen fertility, the overall frequency of chromosome aberrations, and the number of induced fragments. The use of other parameters displays the trend only partially or does not display it at all, as is the case with the use of rarer types of chromosomal rearrangements. The least promising forms have also been identified for use as starting material in treatments with this substance. It is demonstrated that, in general, this agent is characterized by the same patterns in the induction of cytogenetic activity as for other chemical super mutagens, with some variations depending on the starting material. In the future, it is planned to link the obtained data with the frequency and quality of the resulting hereditary changes, primarily complex biochemical and physiological ones, in order to improve the quality of plant products and various types of plant tolerance to adverse environmental conditions. Дослідження цитогенетичних параметрів активності нових мутагенних факторів має на меті достовірне встановлення можливостей цих факторів щодо варіабельності залежно від суб’єкта мутагенної дії, оптимального використання певних розмірів факторів, поєднання обраного протоколу з оптимізацією вихід мутантних форм у майбутньому. Насіння восьми сортів озимої пшениці (Балатон, Боровиця, Зелений Гай, Золото України, Каланча, Нива Одеська, Полянка, Почайна) обробляли СК (азид натрію) у концентраціях 0,010 %, 0,025 %, 0,05 %, 0,10 %. Їх замочували у водному розчині на 24 години. Цитогенетичну активність оцінювали за стерильністю пилку, оцінкою загальних показників і показників спектрів хромосомних аномалій на середніх фазах мітозу клітин за сортом пшениці та концентраціями хімічних речовин. У результаті дослідження продемонстровано ключове значення генотип-мутагенної взаємодії в межах варіабельності основних показників частоти та спектру хромосомних аберацій. Встановлено, що в перспективі оптимальніше буде використовувати два сорти, показники генотипо-мутагенної специфічності яких значно вищі, і від них у майбутньому слід очікувати більшого виходу перспективних мутантних форм, особливо в поєднанні з концентраціями СК. в діапазоні 0,025% і 0,05%. Показано, що основними параметрами, які відображають генетично детерміновані можливості сприйнятливості до екогенетичного чинника, є фертильність пилку, загальна частота хромосомних аберацій та кількість індукованих фрагментів. Використання інших параметрів відображає тренд лише частково або не відображає його зовсім, як у випадку з використанням більш рідкісних типів хромосомних перебудов. Також були визначені найменш перспективні форми для використання як вихідного матеріалу при обробці цією речовиною. Показано, що в цілому цей агент характеризується тими ж закономірностями індукції цитогенетичної активності, що й інші хімічні супермутагени, з деякими варіаціями залежно від вихідного матеріалу. У подальшому планується пов’язати отримані дані з частотою та якістю виникаючих спадкових змін, насамперед складних біохімічних та фізіологічних, з метою підвищення якості рослинної продукції та різних видів толерантності рослин до несприятливих умов зовнішнього середовища.
Генотип-мутагенна взаємодія в цитогенетичній мінливості озимої пшениці для нового екогенетичного чинника
Keywords: cereals; зернові; chromosomal abnormalities; хромосомні аномалії; sodium azide; азид натрію; pollen sterility; стерильність пилку; cytogenetic analyze; цитогенетичний аналіз; site-specific activity; специфічна для сайту діяльність; mutagenesis; мутагенез